Probing Birth-Order Effects on Narrow Traits Using Specification-Curve Analysis. (December 2017) - Rohrer, Julia M.; Egloff, Boris; Schmukle, Stefan C.
The idea that birth-order position has a lasting impact on personality has been discussed for the past 100 years. Recent large-scale studies have indicated that birth-order effects on the Big Five personality traits are negligible. In the current study, we examined a variety of more narrow personality traits in a large representative sample ( n = 6, 500–10, 500 in between-family analyses; n = 900–1, 200 in within-family analyses). We used specification-curve analysis to assess evidence for birth-order effects across a range of models implementing defensible yet arbitrary analytical decisions (e.g., whether to control for age effects or to exclude participants on the basis of sibling spacing). Although specification-curve analysis clearly confirmed the previously reported birth-order effect on intellect, we found no meaningful effects on life satisfaction, locus of control, interpersonal trust, reciprocity, risk taking, patience, impulsivity, or political orientation. The lack of meaningful birth-order effects on self-reports of personality was not limited to broad traits but also held for more narrowly defined characteristics.